Aplikasi Bioleaching Dalam Pemisahan Logam dari Batuan Mineral Pyrite dengan Menggunakan Bakteri Thiobacillus ferooxidans dan Fungi Aspergillus niger - Ronny Kurniawan (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Pyrite (FeS2) is one of the types of sulphide minerals which are common in the nature. Many methods can be used to separate the metal content in pyrite, either chemical treatment, biological treatment, and physical treatment. This study generally aims to study the process of extracting metals Fe, Zn, and Al in the mineral pyrite using bioleaching process, and specifically aims to determine the effect of time and type of microorganisms based on the concentration and yield of the extraction and to study the effect of microorganisms on the selectivity of the metals extracted in the process of the mineral pyrite bioleaching. Parameters used are microorganisms volume (20% of the total volume of work), bioleaching temperature (35°C), the speed of stirrer (70 rpm) and time of bioleaching (10, 20, and 30 days); the type of the analyzed metal are Al, Zn, Fe; and the type of microorganism are Thiobacillus ferooxidans bacteria and Aspergillus niger fungi. The used analysis are AAS and ICP / MS. The result revealed that the time of bioleaching makes some effect on metal concentration in rafinat.The longer time of bioleaching can give the greater value on metal concentration in rafinat. The highest metal concentrations in the rafinat obtained at 759 ppm for the Al using a Thiobacillus ferooxidans bacteria. The highest yield in the rafinat obtained at 15,021% for the Zn using a Thiobacillus ferooxidans bacteria. Generally, Thiobacillus ferooxidans bacteria is better for extracting metals; Fe, Zn, and Al.